German guidelines for psychosocial counselling in the area of “cross border reproductive services” - Thorn, Petra; Wischmann, Tewes (Archives of gynecology and obstetrics, 2013)
An increasing number of couples and individuals with a desire for a child travel abroad for assisted reproductive technologies that are not available in their home country. This trend has been coined “cross border reproductive services” (CBRS), often comprising third party reproduction. In order to respect the welfare of all parties involved, the German Society for Fertility Counselling has developed guidelines for psychosocial counselling in this area in 2010. The following article raises some of the controversies in CBRS and introduces these guidelines.
Published online: 20 October 2012
Gesehen am 03.02.2022